2013
DOI: 10.3899/jrheum.121004
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Phenotypes of Knee Osteoarthritis by Separate Quantitative Radiographic Features May Improve Patient Selection for More Targeted Treatment

Abstract: Five phenotypes of radiographic progression of early knee OA were identified using separate quantitative features, which were associated with baseline radiographic features. Such phenotypes might require specific treatment and represent relevant subgroups for clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 39 publications
0
25
0
Order By: Relevance
“…Recently Kinds et al demonstrated that different radiographic phenotypes of OA may exist. The phenotype designated as 'bone phenotype' in which bone changes predominate over cartilage changes, during 5 years follow-up, could be distinguished from the other phenotypes by clinical and radiographic characteristics at baseline with an AUC ROC of 0.91 59 . If such clear phenotypes cannot even be identified with, in this case bone, markers, it might be questioned whether such markers would be of use in a general population.…”
Section: Treatment Efficacy Evaluated By Biochemical Marker Analysesmentioning
confidence: 99%
“…Recently Kinds et al demonstrated that different radiographic phenotypes of OA may exist. The phenotype designated as 'bone phenotype' in which bone changes predominate over cartilage changes, during 5 years follow-up, could be distinguished from the other phenotypes by clinical and radiographic characteristics at baseline with an AUC ROC of 0.91 59 . If such clear phenotypes cannot even be identified with, in this case bone, markers, it might be questioned whether such markers would be of use in a general population.…”
Section: Treatment Efficacy Evaluated By Biochemical Marker Analysesmentioning
confidence: 99%
“…Other OA associated processes (e.g., osteophytes, subchondral bone changes, and trabecular structure) can likewise be assessed by MRI [13]. With MRI, different phenotypes of OA can be identified and the success of treatment may be tailored depending on the phenotype and its effect can be monitored in more detail [25].…”
Section: Clinical Needsmentioning
confidence: 99%
“…From this list, 25 articles matched the inclusion criteria and were included in the systematic review ( Fig. 1) [7][8][9]. For an overview of the studies included see Table 2.…”
Section: Description Of the Included Studiesmentioning
confidence: 99%
“…One further study with high risk of bias reported similar findings. Among these seven studies, a combination of magnetic resonance imaging (MRI) and biomarkers (serum cartilage oligomeric protein [sCOMP] , N-terminal propeptide of collagen IIA [PIIANP]) [21]; x ray and clinical data [9,27], and cluster analysis (upper leg muscle strength, body mass index (BMI), severity of radiographic OA, depressive mood, radiographic scores of OA features, regional quantitative MRI measures of cartilage and bone, and selfreported knee symptoms) [7,36] were used to determine the severity of the disease. Subjects were classified in this phenotype according to the actual status of the disease and the long term outcome (2-10 years).…”
Section: Minimal Joint Diseasementioning
confidence: 99%
See 1 more Smart Citation